2016
DOI: 10.1007/978-3-662-54110-4_29
|View full text |Cite
|
Sign up to set email alerts
|

Coverage, Matching, and Beyond: New Results on Budgeted Mechanism Design

Abstract: We study a type of reverse (procurement) auction problems in the presence of budget constraints. The general algorithmic problem is to purchase a set of resources, which come at a cost, so as not to exceed a given budget and at the same time maximize a given valuation function. This framework captures the budgeted version of several well known optimization problems, and when the resources are owned by strategic agents the goal is to design truthful and budget feasible mechanisms, i.e. elicit the true cost of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…inferred from[3] and Lemma D.2). Mech-SM-frac is deterministic, truthful, individually rational, budget-feasible, and has approximation ratio ρ + 2 + ρ 2 + 4ρ + 1.Also, it runs in polynomial time as long as the exact algorithm for the relaxed problem runs in polynomial time.Mech-SM-frac(A, v, c, B)1 Set A = {i | c i ≤ B} and i * ∈ arg max i∈A v(i) 2 if ρ + 1 + ρ 2 + 4ρ + 1 · v(i * ) ≥ opt f (A {i * }, B) Greedy-SM(A, v, c, B/2)Note that when the relaxed problem is the same as the original (ρ = 1), then Mech-SMfrac becomes Mech-SM and the two approximation ratios coincide.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…inferred from[3] and Lemma D.2). Mech-SM-frac is deterministic, truthful, individually rational, budget-feasible, and has approximation ratio ρ + 2 + ρ 2 + 4ρ + 1.Also, it runs in polynomial time as long as the exact algorithm for the relaxed problem runs in polynomial time.Mech-SM-frac(A, v, c, B)1 Set A = {i | c i ≤ B} and i * ∈ arg max i∈A v(i) 2 if ρ + 1 + ρ 2 + 4ρ + 1 · v(i * ) ≥ opt f (A {i * }, B) Greedy-SM(A, v, c, B/2)Note that when the relaxed problem is the same as the original (ρ = 1), then Mech-SMfrac becomes Mech-SM and the two approximation ratios coincide.…”
mentioning
confidence: 89%
“…Later, Chen et al [10] significantly improved Singer's results, obtaining a randomized 7.91-approximation mechanism and a deterministic 8.34-approximation mechanism for non-decreasing submodular functions. Several modifications of the mechanism by [10] have been proposed that run in polynomial time for special cases [31,19,3]. For subadditive functions, Dobzinski et al [12] suggested a randomized O(log 2 n)-approximation mechanism, and they gave the first constant factor mechanisms for non-monotone submodular objectives, specifically for cut functions.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations